On the compilation of labour force statistics for Nigeria - Yemi Kale; Sani I. Doguwa (CBN Journal of Applied Statistics, 2015)
Computing unemployment rate using a 40 hours a week benchmark implies that any person who has worked for less than 40 hours during the reference week is considered unemployed. This method has become outdated given the present realities of the working environment in Nigeria, particularly, considering the nature of certain activities in the service sector of the economy. This document presents the new definition and revised methodology that is used to re-compute the labour force statistics in Nigeria between 2010 to 2014 Q4. The high rate of underemployment among age "25-34" years showcased the difficulty associated with youth and graduate unemployment. This is particularly worrisome because this category falls within the very active labour force population. Policies that will address youth and graduate unemployment phenomenon in the country are, therefore, required.
Keywords: E41; C22; 330; Labour Force Statistics; House Hold Labour Force Survey